High-Dimensional Quantum Key Distribution in Quantum Access Networks - Osama Elmabrok; Mohsen Razavi; Tawfig Eltaif; Khaled A. Alaghbari (IEEE Photonics Journal, 2024)
We investigate the use of high-dimensional quantum key distribution (HD-QKD) for wireless access to hybrid quantum-classical networks. We use $d$ -dimensional time-phase encoded states to exchange a secret key between an indoor wireless user and the central office on the other end of the access network. We evaluate the performance in the case of transmitting quantum and classical signals over the same passive optical network by accounting for the impact of background noise induced by the Raman-scattered light on the QKD receiver. We also take into account the loss and background noise that occur in indoor environments as well as finite key effects in our analysis. By studying the system under nominal simulation conditions, we identify regimes of operation in which an HD-QKD system with $d=4$ can outperform its qubit-based counterpart.